Numerical study of transport in a dissipative medium - Barone, P. M.V.B.; Smith, C. Morais [UNESP]; Galvo, D. S. (American Physical Society (APS), 1992)
A numerical study of propagation of a particle through a one-dimensional dissipative medium is presented. The medium is composed of several dissipative sections, which are characterized by their friction coefficients . In particular, we have considered two types of friction coefficients distributed orderly or disorderly along the chain. For the same relative proportion of the coefficients, we have found that 2 transport can be enhanced in the disordered distribution in comparison with the ordered one. We also show how this can be considered an approximated way to treat the propagation in a dissipative medium with a position-dependent friction coefficient. © 1992 The American Physical Society.